Radiological Characteristics of Thalamic Lesions in children and their implications: an in-depth Cross-Sectional Investigation in a Tertiary Care Government Facility - Marya Hameed; Muhammad Fazal Hussain Quershi; Samra Salman (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The thalamus’ main activities are sensory processing, motor control, and consciousness regulation. Aim: To identify connections between radiological characteristics and thalamic damage, which will help develop early diagnostic methods and improve thalamic lesion treatment. Methods: A retrospective cross-sectional single-center study was performed in the Radiology department of the National Institute of Child Health, Karachi, Pakistan. Data was collected over 2.5 years. Non-probability consecutive sampling was utilized to acquire data. The study comprised 197 patients who met the inclusion criteria. A validated questionnaire was used to collect data regarding thalamic lesion symptoms and MRI features. Results: The mean child age was 8.4 years, with a 3-year standard deviation. The patient population was 65.2% male and 34.3% female. The difference between the onset of symptoms and diagnosis of disease was two months on average. 45% of children experienced developmental delays. Among the most prevalent diagnoses were acute ischemia infarction, posterior reversible encephalopathy syndrome, Canavan disease, acute necrotizing encephalitis, and neurofibromatosis. MRI characteristics of thalamic lesions significantly correlated with neurological symptoms. In contrast to etiologies, MRI findings were significantly related. The Majority of the cases were bilateral, having significant results with perilesional edema, signal dropout, diffusion restriction, extra thalamic extension, basal ganglia involvement, and vascular involvement. Conclusion: This article examines the correlation between clinical symptoms, possible causes of thalamic lesions, and imaging findings. Several large-scale investigations are needed to further settle on a clear association between MRI features and thalamic lesions in the pediatric population, as there was ample significance between the variables stated above. Keywords: Thalamus, magnetic resonance imaging, tumors, children